Experimental characterization of thermal hydraulic performance of louvered brazed plate fin heat exchangers - Antonio Bula-Silvera; John Turizo-Santos; Oscar Barros-Ballesteros; Armando Fontalvo-Lascano; Ricardo Vasquez-Padilla (Revista Facultad de Ingeniería Universidad de Antioquia, 2015)
Louvered fins are commonly used in compact heat exchangers to increase the surface area, turbulence, and initiate new boundary layer growth required to improve the heat transfer performance without a significant increase in pressure drop compared with other fins. An experimental study on the air side heat transfer and pressure drop characteristics for a louvered fin with symmetrical pattern in brazed plate heat exchangers has been performed. Reynolds numbers ranged from 350 – 1270, based on the louver pitch while a constant 1.82 m3/h water flow was held. The heat transfer and pressure drop for the geometry tested was reported in terms of Colburn factor (j) and Fanning friction factor (f) as a function of the Reynolds number. The experimental results for j and f are in good agreement compared to regression models suggested for compact heat exchanger with louvered fin and flat tubes, obtaining a deviation of 5.48% and 5.39% respectively. Moreover, when compared to CFD analysis for the same geometry, an average deviation of 6.3% is obtained. Finally a regression model for j and f factors was attained based on the Reynolds number, presenting a deviation of 1.51% and 2.19% respectively.